A comparison of the influence of flocculent and granular structure of sludge on activated carbon: preparation, characterization and application. Issue 90 (13th September 2016) - Liu, Ting; Wei, Dong; Zhang, Ge; Hu, Lihua; Du, Bin; Wei, Qin
Abstract : The novelty of the work is the influence of sludge structure on activated carbon preparation, characterization and application. Abstract : The objective of the present study was to evaluate the influence of the flocculent and granular structure of sludge on sludge-based activated carbon (AC) preparation, characterization and application. Four kinds of sludge, aerobic activated flocculent sludge (AS), anaerobic activated flocculent sludge (AnS), aerobic granular sludge (AGS) and anaerobic granular sludge (AnGS), were selected as precursors for carbon production by using phosphoric acid activation. The physicochemical properties of prepared ACs were determined by Brunauer–Emmett–Teller (BET) surface area, scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), Thermal Gravimetric Analysis (TGA) and zeta potential analysis. The results implied that sorption equilibrium data of malachite green (MG) adsorbed onto four kinds of AC fitted well with the Langmuir model. Granular sludge ACs expressed higher adsorption capacities than those of flocculent sludge ACs. Electrostatic attraction and surface complexation were two possible mechanisms for MG sorption onto the carbons. The obtained results could provide useful information on the development of ACs from excess sludge as attractive biosorbents for dye removal by considering the type of sludge structure.